The effect of knee angle during isometric training on maximal force and muscle size - Noorkoiv, M.; Nosaka, K.; Blazevich, A. J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
It is known that increases in force production in response to exercise training typically occur at or around the training angle. However, the mechanisms underpinning this angle specificity are not known. The purpose of this study was to investigate the mechanisms underlying the angle-specific strength change after isometric training at short and long muscle lengths. Methods One group (n=8) of young healthy men performed 6 weeks of isometric knee extension training in a flexed position (kneeFlex) corresponding to 80% of their maximal force-angle relationship value (38±4°, 0°=full knee extension). Force was calculated as torque per moment arm (measured using x-ray imaging). Another group (n=8) trained at the corresponding force level in an extended knee position (kneeExt; 88±6°). Subjects trained 3 times a week, 5 sets of 5 repetitions (5 contractions, 5 s rest, 1 min inter-set rest). Maximum torque and the EMG:M-wave ratio were measured at 8 knee angles (30-100°) at 0, 3 and 6 weeks of training. Vastus lateralis (VL) fascicle length was measured with ultrasound and muscle cross-sectional area (CSA) was assessed with MRI at 0 and 6 weeks. Results In kneeExt force increased after 3 wk at 40 and 50° (7.6-6.2%), and after 6 weeks at 30, 40 and 50 deg (9.0-12.2%). In kneeFlex, force increased only from 0 to 6 wk at 30, 40 and 50° (5.7-11.5%). The changes in EMG:M-wave ratio were minimal in both groups, and these changes were not clearly correlated with changes in angle-specific force. Rectus femoris (RF), VL and vastus medialis (VM) CSA increased in a kneeFlex only. Correlation analysis revealed that subjects whose VM and RF CSA increased in distal regions tended to increase force production at short muscle lengths, whereas those who increased in middle and proximal regions of VL tended to increase force at long muscle lengths. Fascicle length increase was variable in both groups and, unexpectedly, only increased significantly in kneeExt (P=0.01). Interestingly, there was a negative correlation between the fascicle length at 0 wk and the change in fascicle length with training (P=0.02). Discussion The results that there is a clear specificity when isometric training has been performed at kneeExt and it is more variable with kneeFlex, are in agreement with the findings from others (Thepaut-Mathieu et al. 1988; Kubo et al., 2005). The mechanisms of angle specificity seem to be a complex interaction amongst many factors, however, variability in kneeFlex appears to be related to region of selective hypertrophy. Further analysis of fascicle length and other factors is needed.